WASTE RECOVERY FROM LEATHER - POP, Răzvan Dumitru; ROȘU, Cristina; MANCIULA, Dorin Iosif; POPIȚA, Gabriela-Emilia; NEMEŞ, Ovidiu (Studia Universitatis Babeș-Bolyai Ambientum, 2016)
This study aims procurement and testing of ways using leather waste from tanneries, by incorporating them into a composite. This new material was subjected tests to determine leachability total chromium and lead in leather waste. Flow of production was as follows: grinding skin, placing the composite composition of a CRT glass waste to replace natural aggregates, own recipes, samples forming and demoulding. The new composite was then subjected to leachability test for total chromium and lead. The primary objective of this study was to achieve a composite material that can be used as material for the construction, in compliance with current standards of construction and environmental legislation. The proposed method of waste recovery skin is viable and beneficial to the environment and provides economic benefits by creating jobs.